Clinical studies in amyotrophic lateral sclerosis. Issue 5 (4th October 2022) - Dorst, Johannes; Genge, Angela
Abstract : Purpose of review: The purpose of this review is to discuss the most important recent clinical studies in amyotrophic lateral sclerosis (ALS), including their impact on clinical practice, their methodology, and open questions to be addressed in the future. Recent findings: This article focuses on studies, which provided either a positive primary endpoint or positive post hoc analysis, including edaravone, sodium phenylbutyrate–taurursodiol, rasagiline, tofersen, and high-caloric, fat-rich nutrition. It also covers recent developments in the design of clinical ALS studies with regard to inclusion criteria, stratification factors, and outcome parameters. Summary: Recent clinical studies have indicated various substances to be considered for treatment of ALS. Edaravone has been approved by the US Food and Drug Association (FDA) but not by the European Medicines Agency (EMA), and further studies testing oral formulations are currently conducted. A follow-up study with sodium phenylbutyrate–taurursodiol is ongoing, while follow-up studies for rasagiline and high-caloric, fat-rich nutrition are planned. A phase III study with tofersen was negative but nevertheless yielded promising results. Important developments regarding the design of clinical ALS studies include the implementation of neurofilament light chain (NfL) levels as a standard outcome parameter and the consideration of progression rate for therapeutic response and stratification.